Design and development of type-1 FBG based high temperature sensor. (1st April 2023) - Khan, R Y M; Ullah, R; Faisal, M
Abstract: Thermal metrology is critical in many high-energy industrial processes to optimize the process efficiency, energy consumption and quality of end product. Here, we present the design and development of a double thimble type standard type-1 fiber Bragg grating (FBG) high temperature sensing probes. Two different probes named probe-1 and probe-2 are developed by encapsulating type-1 FBGs in two stainless steel thimbles with ceramic filling. The probes are experimentally tested in a high temperature box furnace and their responses are interrogated by an optical spectrum analyzer. FBGs encapsulated in both probe-1 and probe-2 exhibited a linear red-shift in their Bragg wavelength with increase in temperature from 30 °C to 700 °C with sensitivities of 13.86 ± 0.1 pm/°C and 14.10 ± 0.2 pm/°C which are 4.8% and 3.16% lower than temperature sensitivity of bare FBG, respectively. A deformation in the Bragg spectrum of probe-1 is observed at temperatures above 500 °C however, probe-2 is found to be thermally stable up to 700 °C. An estimated life-time of about 6 years is offered by the optimized probe-2 with a negligible hysteresis and repeatability of 1°C–5°C.